Epidemiología de la neumonía adquirida en la comunidad - Irizar Aramburu, María Isabel (Aten Primaria, 2013)
AIM: To determine the incidence rate, hospital admission, their mortality related factors in community-acquired pneumonia (CAP) in adults in Gipuzkoa. PATIENTS AND METHODS: Prospective observational multicenter study of patients over 14 years-old with CAP treated by 33 primary care physicians for a year. Confirmation of the radiologist for diagnosis of pneumonia was required. The participating physicians collected the sociodemographic and clinical variables of all patients with CAP seen in the clinic during one year, and followed-up on the 2 nd, 10th and 40th day. Same variables were collected from patients who had CAP in the study period and were diagnosed elsewhere. RESULTS: The number of patients over 14 years old with CAP during the study was 406 for a population of 48,905 inhabitants. The incidence of CAP was 8.3 cases per 1000 inhabitants/year, and included 56% males and 44% females. The mean age was 56.2 years. The rate of hospital admission during the study period was 28.6% and was not related to comorbidity or age. The overall mortality rate was 2.7% with a mean age of 83.7 years, and was only related to age. CONCLUSIONS: The incidence of CAP was 8.3 cases per 1000 inhabitants per year. Just over one in four CAP required hospitalization and 2.7% of patients with CAP died. Only age was related to mortality.